The design and optimization of concentrating solar system in Wuhan based on clear sky model. Issue 2 (March 2021) - Mao, Qianjun; Yang, Yizhi; Li, Tao
Abstract: To slow down fossil energy usage and protect the environment, concentrating solar power has experienced tremendous growth. This paper focused on the relationship between annual solar irradiation and tilt angle of the concentrating system to find the optimal tilt angle when annual solar irradiation is maximum. In the calculating process, the tilt angle between 0° and 90° is separated from several angles with a 5° interval and calculate the corresponding annual solar irradiation. A relationship line between solar irradiation and tilt angle is indicated, and the optimal tilt angle is discovered. The relationship between solar irradiation and tilt angle in different seasons is also investigated. The result of this paper would be a theoretical foundation to promote the application of concentrating solar systems in Wuhan.